Track Detection Technique Using CR-39 for Determining Depleted Uranium in Biological Specimens - Shakir M. Murbat Al-jobori (Journal of Madenat Alelem University College, 2013)
Track detecting technique using CR-39 track detector has been implemented for determining depleted uranium concentration in biological specimens (tissues, bones, and blood) of patients infected with cancer diseases. Results were compared with specimens of patients infected with conventional diseases (noncancerous). Specimens were collected from middle and south of Iraq have been contaminated with depleted uranium in the Gulf war in 1991. Results show that this technique is efficient for determining depleted uranium concentration in biological specimens. It was found that all studies samples determine for patients infected with cancer diseases contain a high concentration of depleted uranium (more than the international standard) comparing with noncancerous diseases. Moreover, it was found that persons infected with Leukemia show more sensitive to uranium concentrations to induce the diseases (66-202 ppb), while (116- 1910 ppb) concentrations were needed for inducing cancer diseases in organs and tissues. Result confirmed the correlation between cancerous diseases and the munitions made of depleted uranium used in the Gulf war in 1991 leads to contaminate the Iraqi environment and causes a high risk against people in Iraq.